2012
DOI: 10.1186/1746-6148-8-150
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bone marrow and adipose tissue-derived canine mesenchymal stem cells

Abstract: Background: Bone marrow-derived mesenchymal stem cells (BM-MSCs) and adipose tissue-derived mesenchymal stem cells (AT-MSCs) are potential cellular sources of therapeutic stem cells. MSCs are a multipotent population of cells capable of differentiating into a number of mesodermal lineages. Treatment using MSCs appears to be a helpful approach for structural restoration in regenerative medicine. Correct identification of these cells is necessary, but there is inadequate information on the MSC profile of cell su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
106
1
16

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(145 citation statements)
references
References 42 publications
16
106
1
16
Order By: Relevance
“…This result agrees with the findings of others in equine MSCs (9), being coexpressed by more than the 92% of the cells (10). A high percentage of MSCs from other species such as canine, ovine, or porcine also display in their cell surface these molecules (11)(12)(13).…”
supporting
confidence: 92%
“…This result agrees with the findings of others in equine MSCs (9), being coexpressed by more than the 92% of the cells (10). A high percentage of MSCs from other species such as canine, ovine, or porcine also display in their cell surface these molecules (11)(12)(13).…”
supporting
confidence: 92%
“…Therefore, one should consider the known differences in features of MSCs from different species. As in equine MSCs, CD 29 and CD 44 expressions are found consistently in canine (34,35,51,52), ovine (53), and porcine (54) MSCs. Corresponding to the equine antigen expression profile as well, CD 73 could not be detected in canine, rabbit, or sheep MSCs (35,55,56), while rat tendon derived, feline and bovine neonatal cell sources and caprine bone marrow-derived MSCs expressed this antigen (57)(58)(59)(60).…”
Section: Discussionmentioning
confidence: 73%
“…Most recently, characterization of canine A-MSCs and BM-MSCs identified that canine A-MSCs and BM-MSCs both demonstrated strong expression of CD29 and CD44, moderate expression of CD90, and were negative for CD34 and CD45. Oct3/4 and Sox2 were equally expressed in canine A-MSCs and BM-MSCs, while Nanog expression was 2.5-fold higher in A-MSCs than in BM-MSCs [52]. Markers of human A-MSCs include STRO-1, CD146, and 3G5, in which the 3G5-positive fraction demonstrated the greatest enrichment for CFU-F compared with the other sorted cell populations [53].…”
Section: Differences Between Adipose-and Bone Marrow-derived Mscsmentioning
confidence: 93%